(untitled) (Research, Society and Development, 2021)
This article aims to understand the main challenges that lead parents/guardians of children aged 0 to 5 years to not comply with the vaccination schedule and its associated factors. This is an integrative literature review in LILACS databases, Virtual Health Library / BIREME, Scielo, MEDLINE and Nursing database. The following health descriptors were used: vaccines, vaccination coverage, children and public health, applying the Boolean operator “AND”. After applying the inclusion and exclusion criteria, 394 articles were located, consisting of a final sample of 10 articles. In view of the results, the reasons for parents and/or guardians not to vaccinate children aged 0 to 5 years were: judging the vaccines as unnecessary, fear of side effects and opting for natural lifestyles. In addition to the existence of factors that interfere in this process, such as the absence of immunobiologicals and family culture, the main ones. In this way, parents and/or guardians who mentioned that they thought the vaccines were unnecessary, had doubts about their effectiveness, clung to incomplete sources of information, which was a barrier to be resolved. On the other hand, the public health service needs to improve, as in the provision of immunobiologicals for primary care services, ensuring that stocks remain stocked so there is no shortage of them.